2017
DOI: 10.1016/j.immuni.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Therapeutic Relevance of Neuro-immune Communication

Abstract: Active research at the frontiers of immunology and neuroscience has identified multiple points of interaction and communication between the immune system and the nervous system. Immune cell activation stimulates neuronal circuits that regulate innate and adaptive immunity. Molecular mechanistic insights into the inflammatory reflex and other neuro-immune interactions have greatly advanced understanding immunity, and identified new therapeutic possibilities in inflammatory and autoimmune diseases. Recent succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
359
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 480 publications
(398 citation statements)
references
References 162 publications
5
359
0
8
Order By: Relevance
“…Somatosensory neurons have their peripheral axons in the skin, joints, and muscles, whereas visceral neurons innervate the gastrointestinal tract, liver, pancreas, lungs, heart, and other organs. Both types of neurons project to the spinal cord via the dorsal horn and synapse with interneurons and relay neurons transmitting the signals to the brain (17, 18). Vagus nerve sensory (visceral) neurons are localized in the nodose and jugular ganglia.…”
Section: Neurocentric Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Somatosensory neurons have their peripheral axons in the skin, joints, and muscles, whereas visceral neurons innervate the gastrointestinal tract, liver, pancreas, lungs, heart, and other organs. Both types of neurons project to the spinal cord via the dorsal horn and synapse with interneurons and relay neurons transmitting the signals to the brain (17, 18). Vagus nerve sensory (visceral) neurons are localized in the nodose and jugular ganglia.…”
Section: Neurocentric Perspectivesmentioning
confidence: 99%
“…Ongoing research provides important insight into neuro-immune communication with translational relevance (18, 113). In this section we briefly outline current clinical studies stemming from this research and exploring relevant pharmacological modalities and bioelectronic neuromodulation as novel therapeutics for inflammatory and autoimmune conditions.…”
Section: Clinical Translation Of Neuroscience In Inflammatory Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Latest advances have shown that the nervous system has a close relationship with the immune system, and neuroimmune communications are essential to regulate immune function in response to pathological conditions [12, 13]. The sympathetic nervous system (SNS) communicates with all cells of the immune system, regulating their function through the release of norepinephrine (NE), and activating intercellular signaling pathway via the adrenergic receptors (ARs) expressed on immunocytes [13, 14].…”
Section: Introductionmentioning
confidence: 99%